An Effective Intervention: Limiting Opioid Prescribing as a Means of Reducing Opioid Analgesic Misuse, and Overdose Deaths. Issue 2 (June 2020) - Fink, Brandi C.; Uyttebrouck, Olivier; Larson, Richard S.
Overdose deaths involving prescription opioids killed more than 17, 000 Americans in 2017, marking a five-fold increase since 1999. High prescribing rates of opioid analgesics have been a substantial contributor to prescription opioid misuse, dependence, overdose and heroin use. There was recognition approximately ten years ago that opioid prescribing patterns were contributing to this startling increase in negative opioid-related outcomes, and federal actions, including Medicare reimbursement reform and regulatory actions, were initiated to restrict opioid prescribing. The current manuscript is a description of those actions, the effect of those actions on opioid prescribing and related patient outcomes. We also describe our proposal of methods of expanding these efforts as an important piece to further reduce opioid-related misuse, dependence, and overdose death.